Implementation of the Qur'an Tahfidz Learning Method at the Nurul Huda Islamic Boarding School - Andriani, Ria; Khairudin, Fiddian; Nasrullah, Nasrullah (Universitas Pahlawan Tuanku Tambusai, 2026)
The background of this research is that as Muslims, of course, we have a responsibility, namely to maintain and care for the Qur'an. One form of care is to memorize it. This study seeks to explain the implementation of learning at the Nurul Huda Islamic Boarding School with three main objectives, namely describing local content activities in the Islamic boarding school, tracing the methods used in the Tahfidz Qur'an program, and identifying factors that support and hinder the achievement of memorization of students. The approach used is qualitative so that researchers can understand the learning process more deeply through observation, interviews, and document review. The findings of the study show that local content activities are designed to form students into a generation that adheres to Islamic values based on the Qur'an and hadith. The Tahfidz Qur'an program at the Nurul Huda Islamic Boarding School applies several methods, such as the wahdah method, sima'i, repetition of each verse, and muraja'ah as a general strengthening of memorization. These methods help students strengthen memorization gradually and continuously.